Los proyectos de instauración de tribunales de la Inquisición en la frontera urbana colonial de la región «platina»: Tucumán y Río de la Plata (siglos XVII-XVIII) - Vassallo, Jaqueline (2019)
In this work we address proposals for the creation of Inquisition courts by inquisitorial, royal, and ecclesiastical authorities, between the 17th and 18th centuries, due to the immense territorial extension of the Lima court’s jurisdiction, and the problems that derived from it. This study specially focuses on the governorates of Tucumán and Rio de la Plata, as part of the so-called «región platina», a space linking population centers of the colonial urban borderland shared by Portuguese, Castilians, Spanish Creoles, and Portuguese Americans.